'A few sparks of inspiration'?: analysing the outcomes of European Union cultural policy coordination. Issue 1 (1st January 2018) - Mattocks, Kate
ABSTRACT: This article examines the outcomes of cultural policy coordination in the European Union using a case study of one policy priority in the 2011–2014 Work Plan for Culture. The Open Method of Coordination brings Member States together to exchange and cooperate on key policy priorities. Drawing on interviews with key actors as well as participant observation material, the article demonstrates the limited influence of the culture OMC on domestic policy, showing that domestic usage tends to be on the scale of individuals and organisations rather than Member State-wide. The article finishes by contextualising the outcomes, highlighting the constraints and challenges of intergovernmental coordination in fields where the EU holds a supporting competence.